2022
DOI: 10.1007/s12144-021-02544-3
|View full text |Cite|
|
Sign up to set email alerts
|

The link between the brain volume derived index and the determinants of social performance

Abstract: Motivation, defined as the energizing of behavior in pursuit of a goal, is a fundamental element of our interaction with the world and with each other. Furthermore, as it is known that cooperation leads to higher levels of performance than do individual conditions, empathic concern is also crucial to all forms of helping relationships. A growing number of studies indicate that motivation and empathy are associated not only with organizational performance and study achievements, but also with the human brain. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 82 publications
1
8
1
Order By: Relevance
“…In any case, it can be said that happiness and well-being do not tend to decrease consistently with age, which is almost common in many studies. This is seemingly inconsistent with studies showing that the brain atrophies with age [21][22][23][24][25][26] , and studies showing that the brain correlates with happiness [27][28][29][30][31] .…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…In any case, it can be said that happiness and well-being do not tend to decrease consistently with age, which is almost common in many studies. This is seemingly inconsistent with studies showing that the brain atrophies with age [21][22][23][24][25][26] , and studies showing that the brain correlates with happiness [27][28][29][30][31] .…”
Section: Discussioncontrasting
confidence: 61%
“…See Nemoto et al (2017) 21 for more information. In our previous studies, whole-brain level GM-BHQ showed a positive correlation with dietary balance 23 ,curiosity 24 , and behavioral activation 27 as well as negatively correlated with fatigue 25 and unhealthy lifestyles 26 . Similarly, it was shown that whole-brain FA-BHQ was positively correlated with cognitive function, fish diet intake 22 , housing quality, and anxiety 76 .…”
Section: Mri Data Acquisitionmentioning
confidence: 83%
See 2 more Smart Citations
“…Second, 116 regional GM quotients were averaged to produce the participant-specific GM-BHQ according to the database of Nemoto et al (2017). The graphical flowchart of how GM-BHQ is calculated was shown in a previous study [ 51 ].…”
Section: Methodsmentioning
confidence: 99%